2002
DOI: 10.3168/jds.s0022-0302(02)74278-1
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory and Inhibitory Effects of Protein Amino Acids on Growth Rate and Efficiency of Mixed Ruminal Bacteria

Abstract: Mixed ruminal bacteria were incubated in vitro with glucose, xylose, cellobiose, and various protein amino acids replaced isonitrogenously with 25% (i.e., 25 mg of N/L) of ammonia-N, to determine the growth rate and the amount of sugar consumed in the exponential growth phase. The growth rate and efficiency (grams of bacteria per gram of sugars) increased by 46 and 15%, respectively, when a mixture of 20 amino acids was added. On the other hand, neither growth rate nor efficiency increased when any one of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 34 publications
1
60
2
1
Order By: Relevance
“…Thus, when glutamine is administered enterally, multiple pathogens residing in the gastrointestinal tract have access to it and its benefits. The growth rate of mixed luminal bacteria, for example, was found to increase when exposed to high levels of glutamine (24). This theory may also explain why parenteral glutamine supplementation has been shown more definitively to have a positive effect on mortality rate as the glutamine is not being introduced directly to the bacteria in the gut flora.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, when glutamine is administered enterally, multiple pathogens residing in the gastrointestinal tract have access to it and its benefits. The growth rate of mixed luminal bacteria, for example, was found to increase when exposed to high levels of glutamine (24). This theory may also explain why parenteral glutamine supplementation has been shown more definitively to have a positive effect on mortality rate as the glutamine is not being introduced directly to the bacteria in the gut flora.…”
Section: Discussionmentioning
confidence: 83%
“…Some studies have supported the use of enteral glutamine (2,13,14), primarily for reduction in infectious morbidity (15)(16)(17)(18), whereas others have found no benefit or conflicting results (19 -22). Some authors warn of potential harm (23), and animal studies have demonstrated an increased growth rate of bacteria when incubated in the presence of glutamine (24). The results of studies evaluating the role of parenteral glutamine show a trend toward improved outcomes (2-4, 9, 14).…”
mentioning
confidence: 97%
“…Previous pure culture studies also showed AA being stimulatory to the growth yield of R. albus SY3 and R. flavefaciens 17 (Atasoglu et al, 2001). Also, several experiments conducted with mixed ruminal microorganisms confirm the stimulatory effects of AA on microbial growth (Argyle and Baldwin, 1989;Atasoglu et al, 1999;Kajikawa et al, 2002;Atasoglu et al, 2003).…”
Section: Microbial Yieldmentioning
confidence: 78%
“…However, aromatic AA have been known to limit the growth of microbes and xylan fermentation by mixed rumen micro-organisms (Kajikawa et al, 2002;Atasoglu et al, 2003;Guliye et al, 2005). Phenylalanine, one of the aromatic AA, has been suggested to be essential for the growth of cellulolytic bacterial species, including Ruminococcus (Allison 1965) and Fibrobacter succinogenes (Allison, 1965;Atasoglu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1999). However, aromatic AA have been implicated to limit the growth of and fermentation by mixed rumen micro‐organisms (Kajikawa et al . 2002; Atasoglu et al .…”
Section: Introductionmentioning
confidence: 99%